Speech Act Analysis of Political Discourses: Case Study of Presidents Kagame’s and Weah’s Inaugural Speeches - DADJO, Servais Dieu-Donné Yédia (My University, 2021)
Drawing on Austin’s (1962) Speech Act Theory, this paper investigates Presidents Kagame’s and Weah’s Inaugural Speeches for the purpose of decoding peace-related meanings. The scrutiny of the speeches has revealed that genocide and civil war have caused the death of thousands and thousands civilians. Besides, the predominance of assertive acts in President Weah’s speech has marked both his attachment to democracy and peace and his gratitude and gratefulness to Liberians who long for peace. In President Kagame’s context, the study has shown that assertive acts reveal the president’s capacity to work for the development of Rwanda and his desire to collaborate with other African leaders.
Keywords: Acts; Expressive Acts; Illocutionary Acts; Speech; Acts.